Progress of shrink polymer micro- and nanomanufacturing - Wenzheng He (Nature Publishing Group, 2021)
Abstract Traditional lithography plays a significant role in the fabrication of micro- and nanostructures. Nevertheless, the fabrication process still suffers from the limitations of manufacturing devices with a high aspect ratio or three-dimensional structure. Recent findings have revealed that shrink polymers attain a certain potential in micro- and nanostructure manufacturing. This technique, denoted as heat-induced shrink lithography, exhibits inherent merits, including an improved fabrication resolution by shrinking, controllable shrinkage behavior, and surface wrinkles, and an efficient fabrication process. These merits unfold new avenues, compensating for the shortcomings of traditional technologies. Manufacturing using shrink polymers is investigated in regard to its mechanism and applications. This review classifies typical applications of shrink polymers in micro- and nanostructures into the size-contraction feature and surface wrinkles. Additionally, corresponding shrinkage mechanisms and models for shrinkage, and wrinkle parameter control are examined. Regarding the size-contraction feature, this paper summarizes the progress on high-aspect-ratio devices, microchannels, self-folding structures, optical antenna arrays, and nanowires. Regarding surface wrinkles, this paper evaluates the development of wearable sensors, electrochemical sensors, energy-conversion technology, cell-alignment structures, and antibacterial surfaces. Finally, the limitations and prospects of shrink lithography are analyzed.